2021
DOI: 10.1109/access.2021.3081068
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study of a Fully 3D-Printed Dielectric Resonator Antenna Loaded With a Metallic Cap

Abstract: This article presents a parametric study of a fully 3D-printed hemispherical dielectric resonator antenna (DRA) using low loss dielectric filament and high-conductive filaments jointly with a low-cost customized dual-extruding 3D printer. The parametric study consisted in the design and evaluation of five different hemispherical DRA topologies with different internal shapes and the same overall size, in which the printing infill percentage of the DRA was reduced. A 3D-printed metallic cap was included in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…One technology used in recent years to implement high frequency structures is 3D-printing 10 , 11 . Thanks to the introduction of low-loss dielectric and conductive filaments, together with the lower cost and higher precision of the new generation of 3D-printers, it has been possible to implement different high frequency topologies that were either difficult or too expensive to manufacture 12 , 13 . This brings the opportunity to implement cost-effective solutions.…”
Section: Introductionmentioning
confidence: 99%
“…One technology used in recent years to implement high frequency structures is 3D-printing 10 , 11 . Thanks to the introduction of low-loss dielectric and conductive filaments, together with the lower cost and higher precision of the new generation of 3D-printers, it has been possible to implement different high frequency topologies that were either difficult or too expensive to manufacture 12 , 13 . This brings the opportunity to implement cost-effective solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Changing the 3D-printed infill fraction was also used to create a DRA with two effective dielectric regions. It was found that by increasing the air volume fraction in certain locations and including a metal cap to compensate for the frequency shift, the weight of the DRA could be reduced by 22% [57].…”
Section: Dielectric Resonator Antennasmentioning
confidence: 99%
“…3D printer are a cost-efficient solution for manufacturing of complex microwave designs such as in Garcia-Martinez and colleagues. [27][28][29][30][31][32][33][34][35][36] Here to have a design with a shorter length, the substrates is modeled as nonplanar substrate. This feature can be obtained easily by using the unique feature of 3D printing technology.…”
Section: Design Of Nunpmf Unit Element and Data Setmentioning
confidence: 99%
“…With recent development in 3D printing technology the fields that utilize this method for low‐cost manufacturing is also increased. 3D printer are a cost‐efficient solution for manufacturing of complex microwave designs such as in Garcia‐Martinez and colleagues 27–36 . Here to have a design with a shorter length, the substrates is modeled as nonplanar substrate.…”
Section: Design Of Nunpmf Unit Element and Data Setmentioning
confidence: 99%